Self–Brand Connection and the Decision to Purchase Counterfeit and Original Luxury Brands in Tanzania - Frida Thomas Pacho (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2023)
The research employed the method of Perceived Counterfeit Detection (PCD) to determine the significance of individuals' considerations in determining their decision to purchase original luxury brands. The study explored the relationship between self-brand connection and the purchase of counterfeit luxury brands, and also, evaluated the influence of economic benefits. The research was conducted through a survey of prospective luxury goods consumers, both original and counterfeit, in six malls located in two cities using a questionnaire. A sample of 930 participants was used, and the hypotheses were tested using a structural equation model. The findings indicate that an individual's self-concept might play a role in deciding whether to purchase an original or counterfeit luxury brand. It is noteworthy that the Perceived Counterfeit Detection completely influenced the relationship between self-brand connection and the decision to buy an original luxury brand. Furthermore, the study discovered that economic advantages intensified the inclination of consumers to buy counterfeit products in emerging economies. This contributes to the Social Identity Theory, suggesting that in scenarios heavily influenced by personal development, social pressure from one's social group might override individual moral considerations such as self-brand connection. The findings of this study hold considerable importance for managers and marketers as they enhance their comprehension of the influential role that individuals play in influencing the purchase of luxury brands. Marketing strategies need to consider the influence of family and social groups on buying choices, and advertisements should be customized accordingly.